Microplastics in sediment of Indonesia waters : A systematic review of occurrence, monitoring and potential environmental risks - Said Ali Akbar; Sari Afriani; Cut Nuzlia; Suraiya Nazlia; Sri Agustina (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2023)
Microplastics, or plastic particles smaller than 5 mm, are a growing ecotoxicological problem for both human health and aquatic habitats. Even though microplastic pollution affects the air, water, and land widely, these habitats are often viewed as distinct from one another while in fact they are tightly related. The purpose of this work is to review the body of scientific literature on microplastic studies in Indonesian watershed sediment. Google Scholar has identified around 57 papers about microplastic pollution that were published between 2017 and 2023. Papers about sediment for rivers, lakes, marine, and estuaries are categorized further based on (i) their occurrence and characterization, (ii) their intake by and effects on species, and (iii) their fate and transport issues. Even at low concentrations of 10 g/mL, microplastics cause harmful effects for people and animals, including cytotoxicity, immunological response, oxidative stress, barrier characteristics, and genotoxicity. When marine animals eat microplastics, their gastrointestinal tract physiology changes, and they also experience immune system depression, oxidative stress, cytotoxicity, differential gene expression, and growth inhibition. In addition, the bioaccumulation of microplastics in aquatic creatures' tissues may harm the aquatic ecosystem and may spread to people and birds. Through behavioural changes and policy changes, such imposing taxes, bans, or price increases on plastic carrier bags, plastic usage has been dramatically decreased to 885% in many different nations across the globe. The strategy for minimizing microplastics is structured like an upside-down pyramid: prevention is at the top, then reduction, reuse, recycling, recovery, and, as the least desirable alternative, disposal.Keywords:MicroplasticsSedimentIndonesia WatersEnvironmental RiskPollutant Aquatic